OPTIMIZATION OF CRIMINAL LEGISLATION: REFORMING CRIMINAL PROCEDURAL AND PENAL LAWS (Journal of actual problems of jurisprudence, 2023)
Criminal legislation, which is the cornerstone of legal systems, forms the criminal prosecution, protection and adjudication of criminal cases. This article examines the need to optimize criminal legislation with an emphasis on the reform of criminal procedure and penal enforcement legislation to solve modern problems of crime prevention. This highlights the need to adapt to changing complexities, including cybercrime, terrorism and transnational organized crime, which requires an active review of existing regulations. The protection of human rights is another important factor in reforms, and the principle of proportionality determines efforts to bring legislation into line with international standards. Effective crime deterrence is a central goal based on rational choice theory and is achieved through clear laws, consistent sanctions and public awareness. Case studies from the European Union, Kazakhstan and Japan illustrate different approaches to updating criminal legislation in response to modern challenges. Despite the barriers in the development and enforcement of legislation, this continuous path is necessary to maintain justice, protect human rights and the rule of law in our constantly evolving world.Keywords: criminal legislation, offenses, European Union, human rights, penal laws.